A systematic review of the barriers and facilitators influencing the cancer screening behaviour among people with intellectual disabilities. (February 2022) - Chan, Dorothy N.S.; Law, Bernard M.H.; Au, Doreen W.H.; So, Winnie K.W.; Fan, Ning
Abstract: Individuals with intellectual disabilities (ID) may require assistance in accessing healthcare services, including cancer screening. A better understanding of the factors affecting cancer screening utilisation among these individuals is needed for the development of strategies to promote screening uptake in them. This review aimed to explore the facilitators of and barriers to cancer screening utilisation among people with ID. A literature search was conducted using five databases, and an additional snowball search yielded 16 studies for inclusion in the review. Overall, the methodological quality of these studies was good (43–100%). In this review, we noted barriers to screening among individuals with ID, including perceptions of fear, distress, and embarrassment; unpreparedness for screening; negative interactions with healthcare professionals; a lack of knowledge about cancer screening; mobility issues; a high severity of ID; and a lack of ability to provide consent and communicate verbally. Facilitators to screening among these individuals were also identified, including living in a supervised setting, prior use of other healthcare services, being educated about screening via social media, having carers accompany them to screening appointments, and having dual insurance coverage or a higher income. Our review highlights the current needs of individuals with ID undergoing cancer screening. Strategies should be developed to address these needs, such as the provision of training to healthcare professionals on how to conduct screening for people with ID. Highlights: People with intellectual disability face multiple barriers to cancer screening. Physicians should be trained to conduct cancer screening for these individuals. Cancer screening provision should be augmented based on their unmet needs.